Geometric Primitive Fitting in Large Structure 3D Point Clouds Acquired by Drones - Maurell, Igor P.; Ferreira, Caue; Eguti, Carlos A.; Drews-Jr, Paulo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2021)
Geometric primitive fitting in point clouds of large structures is an important task in many scenarios, such as: 3D data simplification, scene reconstruction and 3D CAD reverse engineering. With the advance in unmanned aerial vehicle technologies, multiple large-scale 3D point clouds are being generated by these systems for many goals. Some of the solutions that emerged with this 3D data high availability can be directly or indirectly benefited by a pipeline that finds the geometric primitives underlying in large-scale 3D point clouds. Thus, the work present a pipeline to completely process those data and fit simple geometric primitives to it. Results showed the capabilities of this type of technique in real world data.